Experimental Study on the Effect of Mooring Line Failure on the Hydrodynamic Behaviour of Spread Moored FPSO - SELVANATHAN, ALAN APOSTLER (Universiti Teknologi PETRONAS, 2020)
This dissertation discusses on idea of performing a physical model test to study on the effect of mooring line failure on the hydrodynamic behavior of spread moored FPSO. This reasoning was initiated due to some critical situation faced by the industry with increasing rate of mooring line failure. Floating Storage and Offloading Production (FPSO) units are common choices for offshore oil and gas projects at deepwater. FPSOs are offshore production facilities which houses equipment for processing and storage for hydrocarbons generated. Floating platforms in deep and ultra-deep water areas are the most viable choice(Raza Ul Mustafa, Guan et al. 2018). Floating structures are designed to retain their place throughout their entire lifespan under harsh environmental conditions. The mooring lines are subjected to very extreme cycles of stress which can lead to line failure.